Argumentasi Inkarsunah tentang Otoritas Sunah: Argumentation of Inkarsunah regarding the Authority of Sunah - Fata, Zahrul; Setiadi, Ugi Agus; Nasution, Alhafidh (Center of Islamic and Occidental Studies, 2023)
Establishing hadith as the second source of law after the Qur'an is a consensus among scholars. However, not everyone has held this view throughout history. One such dissenting opinion is the school of Inkarsunah, which outright rejects the hadith of the Prophet Muhammad (peace be upon him) as an argument. This research aims to dissect the arguments of Inkarsunah in rejecting hadith as a source of Islamic law while addressing the doubts and objections to their arguments. The method employed is descriptive analysis with a literature approach (library research), encompassing the arguments of Inkarsunah and analyzing them through the refutations provided by scholars. The results reveal that there are similarities in the arguments presented by historical and contemporary Inkarsunah. Consequently, what was refuted by al-Shafi‘i and other scholars remains relevant for use in the present time.